Why So Gloomy? : Perceptions of Economic Mobility in Europe and Central Asia - Cancho, César (World Bank, Washington, DC, 2016)
Despite significant improvements in per capita expenditures and a marked decline in poverty over the 2000s, a large fraction of Eastern Europe and Central Asias population reports their economic situation in the late 2000s to be worse than in 1989. This paper uses data from the Life in Transition Survey to document the gap between objective and subjective economic mobility and investigate what may drive this apparent disconnection. The paper aims at identifying some of the drivers behind subjective perceptions of economic mobility, focusing on the role of perceptions of fairness and trust in shaping peoples perceptions of their upward or downward mobility. The results show that close to half of the households in the region perceive to have experienced downward economic mobility, that is, that their position in the income distribution has deteriorated. The results also show that perceptions of higher inequality, unfairness, and distrust in public institutions are associated with downward subjective economic mobility. The findings from this study confirm that factors beyond objective well-being are associated with the perceptions of mobility observed in Europe and Central Asia and may explain why the region has had such a pessimistic view of economic mobility during the past two decades. Understanding what drives peoples perceptions of their living standards and quality of life is important, because regardless of objective measures, perceptions could influence peoples behavior, including support for reforms and labor market decisions. For Eastern Europe and Central Asia, a region that has undergone substantive transformations and which is still going through a reform process, accounting for these aspects is critical.